2017
DOI: 10.1108/mf-07-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

A survey of litigation in corporate finance

Abstract: Purpose: The purpose of this paper is to review research on litigation in corporate finance. Design/methodology/approach: This paper surveys studies on the estimation of litigation risk, litigation costs, stock reaction to lawsuit announcement, and the effect of litigation on corporate financial policies and outcomes. Findings: The first section presents a survey of studies that estimate litigation risk. The authors then discuss a set of studies that focus on the various costs associated with litigation. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…Moreover, some studies suggest that clawback adoption increases accounting quality and strengthens overall governance (Chan et al , 2012; and Iskandar-Datta and Jia, 2013). At the same time, prior literature on litigation shows that better monitoring of management and stronger corporate governance can reduce the incidence of lawsuits (Farber, 2005; Marciukaityte et al , 2006; Ferris et al , 2007; Karpoff et al , 2008; and Arena and Ferris, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some studies suggest that clawback adoption increases accounting quality and strengthens overall governance (Chan et al , 2012; and Iskandar-Datta and Jia, 2013). At the same time, prior literature on litigation shows that better monitoring of management and stronger corporate governance can reduce the incidence of lawsuits (Farber, 2005; Marciukaityte et al , 2006; Ferris et al , 2007; Karpoff et al , 2008; and Arena and Ferris, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, studies on litigation risk and corporate lawsuits have found that the threat of litigation and actual lawsuits can motivate a firm’s decision to improve corporate governance practices (Arena and Ferris, 2017). For example, Romano (1991) and Humphery-Jenner (2012) find that managerial turnover is more common for firms involved in litigation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Whistle blowing procedures are supported because they are considered as part of an organization's internal control. Arena and Ferris, (2017) claimed that the weak legislation is one of the key causes of rising internet fraud; as a result of outdated legalization, criminals take advantage of the opportunity to avoid law enforcement organizations. As a result, the country's latest fraud tactics and laws are also established in accordance with fraud techniques.…”
Section: Causesmentioning
confidence: 99%
“…According to Arena and Ferris (2017), one of the major causes of increasing online fraud is weak legislation; due to outdated legalization, criminals take the advantages to get rid off from the law enforcement agencies. So, keeping in view, the latest fraud techniques laws of the country also are formulated as per fraud techniques.…”
Section: Litigation Supportmentioning
confidence: 99%